Elevating Equity in Transportation Decision Making: Recommendations for Federal Competitive Grant Programs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
There has been a recently large increase in competitive federal grant programs for transportation, and the U.S. Department of Transportation (USDOT) has considerable control over how the programs are structured and the funds awarded to states and other applicants. With this, USDOT has asked TRB and the National Academies to review the ways USDOT can emphasize and promote equity within the competitive grants process.TRB Special Report 348: Elevating Equity in Transportation Decision Making: Recommendations for Federal Competitive Grant Programs from the Transportation Research Board of the National Academy of Sciences, Engineering, and Medicine is the product of an expert committee convened to fulfill this study charge.The findings note that equity needs to be pursued across all facets of USDOT’s competitive grant programs, from goal setting and project evaluations to ensuring that all eligible participants have the capacity to apply for grants and to implement them successfully.
Keywords: Transportation and Infrastructure

Renewing the National Commitment to the Interstate Highway System: A Foundation for the Future - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB Special Report 329: Renewing the National Commitment to the Interstate Highway System: A Foundation for the Future explores pending and future federal investment and policy decisions concerning the federal Interstate Highway System. Congress asked the committee to make recommendations on the “features, standards, capacity needs, application of technologies, and intergovernmental roles to upgrade the Interstate System” and to advise on any changes in law and resources required to further the recommended actions. The report of the study committee suggests a path forward to meet the growing and shifting demands of the 21st century.The prospect of an aging and worn Interstate System that operates unreliably is concerning in the face of a vehicle fleet that continues to transform as the 21st century progresses and the vulnerabilities due to climate change place new demands on the country’s transportation infrastructure. Recent combined state and federal capital spending on the Interstates has been about $20–$25 billion per year. The estimates in this study suggest this level of spending is too low and that $45–$70 billion annually over the next 20 years will be needed to undertake the long-deferred rebuilding of pavements and bridges and to accommodate and manage growing user demand. This estimated investment is incomplete because it omits the spending that will be required to meet other challenges such as boosting the system’s resilience and expanding its geographic coverage.The committee recommends that Congress legislate an Interstate Highway System Renewal and Modernization Program (RAMP). This program should focus on reconstructing deteriorated pavements, including their foundations, and bridge infrastructure; adding physical capacity and operations and demand management capabilities where needed; and increasing the system’s resilience. The report explores ways to pay for this program, including lifting the ban on tolling of existing general-purpose Interstate highways and increasing the federal fuel tax to a level commensurate with the federal share of the required RAMP investment.View the videos, recorded webcast, graphics, summary booklet, press release, and highlights page at interstate.trb.org.
Keywords: Transportation and Infrastructure

Investing in Transportation Resilience: A Framework for Informed Choices - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Significant progress has been made over the last decade in integrating resilience criteria into transportation decision-making. A compelling case remains for investing in making transportation projects more resilient in the face of increasing and intensifying storms, floods, droughts, and other natural hazards that are combining with sea-level rise, new temperature and precipitation norms, and other effects from climate change.TRB’s Special Report 340: Investing in Transportation Resilience: A Framework for Informed Choices reviews current practices by transportation agencies for evaluating resilience and conducting investment analysis for the purpose of restoring and adding resilience. These practices require methods for measuring the resilience of the existing transportation system and for evaluating and prioritizing options to improve resilience by strengthening, adding redundancy to, and relocating vulnerable assets.Supplemental to the report is a Report Highlights three-pager.
Keywords: Transportation and Infrastructure